2023
DOI: 10.1111/1742-6723.14170
|View full text |Cite
|
Sign up to set email alerts
|

Electric scooter‐related trauma, alcohol and other drugs

Abstract: Objective: To report the frequency of electric scooter-related trauma and association with alcohol and other drug (AOD) use. Methods: A retrospective cohort study was conducted, including presentations from 1 January 2017 to 31 May 2022 to a metropolitan health service. Results: There were 272 cases included, with increasing frequency, of which 65 (24%) had AOD exposure. Most AOD-related trauma occurred at night, among males, without helmet use, had higher injury severity, requirement for surgical intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 6 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…In the present study, helmet use was reported by 43% of the current cohort. Our results suggest that e‐Scooter riders who did not wear helmets had an association with increased risk of head injuries, which is in keeping with the current literature 6,8,10,16 . The rate of helmet usage (43%) in the current study is in keeping with the findings in Brisbane, Australia (46%), Tasmania (36%), and Melbourne (18%–31%) 6,8,9 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the present study, helmet use was reported by 43% of the current cohort. Our results suggest that e‐Scooter riders who did not wear helmets had an association with increased risk of head injuries, which is in keeping with the current literature 6,8,10,16 . The rate of helmet usage (43%) in the current study is in keeping with the findings in Brisbane, Australia (46%), Tasmania (36%), and Melbourne (18%–31%) 6,8,9 .…”
Section: Discussionsupporting
confidence: 89%
“…10,16 This intoxication rate is the highest noted in the current literature for the Oceania region, with other studies placing intoxication rates between 23.3% and 27%. 6,7,10 Globally, intoxication rates vary greatly with ranges between 5.2% and 75.7% in studies looking at all types of injuries. 16,29,30 Studies investigating head or ophthalmological injuries in isolation noted helmet use rates were as low as 0% and intoxication rates were as high as 91%.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations